A new genus and new species of Cicadettini (Hemiptera: Cicadidae: Cicadettinae) from Pakistan - Sanborn, Allen F.; Ahmed, Zubair (Zootaxa, 2017)
Pakistan contains parts of the Indomalayan and Palaearctic ecozones. As a result, there is a diversity of habitats that has led to diversity in the cicada fauna. We reviewed the Pakistani cicada fauna (Ahmed and Sanborn 2010) but new records and new species continue to be found (Ahmed et al. 2010; 2012; 2013; 2014). This work continues to expand the knowledge of the Pakistani cicada fauna with the description of a new genus and new species of cicada provided to the second author from his contacts.